Africa: Neo-Capitalism Neo-Colonialism Neo-National Liberation Movement - Mahmoud, Mahgoub El-Tigani (European Scientific Journal, ESJ, 2024)
Africa entered the twenty-first century ’saddled with brain drain, political violence, repression of human rights and the lack of a productive professional and technological environment.’ African armies continued to seize the political power taking advantage of a massive civilian movement motivated by experienced professional and worker trades unions supporting millions of aspiring patriotic youths in need of education, job opportunities, and organizational training. While the glorious legacies of the older generations of DuBois, Nkrumah, Nasir, Mandela, and many other liberal leaderships passed away, a new wave of predominantly youth populations has exceedingly taken the lead, defying neo-capitalism and escalating confrontation with neo-colonialism free of underdevelopment exploitation and abuse of authority, foreign investors from all corners of the planet must salvage the indigenous farmers productive force and the impoverished low-income workers and professionals from long-lasting deprivations.